2019
DOI: 10.1007/s11064-019-02915-0
|View full text |Cite
|
Sign up to set email alerts
|

DHA Attenuates Hypoxia/Reoxygenation Injury by Activating SSeCKS in Human Cerebrovascular Pericytes

Abstract: Docosahexaenoic acid (DHA) can alleviate cerebral ischemia/reperfusion injury by reducing blood-brain barrier permeability and maintaining its integrity, accompanied by an increased Ang-1/Ang-2 ratio; however, the underlying mechanisms of these effects remain unclear. Src-suppressed C kinase substrates (SSeCKS), a substrate of protein kinase C, plays an important role in maintaining cell junctions and cell morphology and regulating cell permeability. However, whether DHA can increase SSeCKS expression and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In rat brain microvascular endothelial cells under an oxygen- and glucose-deprivation environment (OGD), that mimics ischemic stroke in vitro, DHA was shown to decrease apoptosis, COX-2 protein expression, and the secretion of PGE 2 , PGI 2 , vascular endothelial growth factor (VEGF), and angiopoietin-2 (Ang-2, which has been shown to cause blood–brain barrier damage and to increase endothelial cell apoptosis) [ 123 ]. DHA can also decrease hypoxia/reoxygenation injury by activating Src-suppressed C kinase (SSeCKS), a substrate of protein kinase C that plays a key role in maintaining cell morphology and tight junctions of the blood–brain barrier and regulating cell permeability [ 124 , 125 ].…”
Section: Lipids and Ischemic Strokementioning
confidence: 99%
“…In rat brain microvascular endothelial cells under an oxygen- and glucose-deprivation environment (OGD), that mimics ischemic stroke in vitro, DHA was shown to decrease apoptosis, COX-2 protein expression, and the secretion of PGE 2 , PGI 2 , vascular endothelial growth factor (VEGF), and angiopoietin-2 (Ang-2, which has been shown to cause blood–brain barrier damage and to increase endothelial cell apoptosis) [ 123 ]. DHA can also decrease hypoxia/reoxygenation injury by activating Src-suppressed C kinase (SSeCKS), a substrate of protein kinase C that plays a key role in maintaining cell morphology and tight junctions of the blood–brain barrier and regulating cell permeability [ 124 , 125 ].…”
Section: Lipids and Ischemic Strokementioning
confidence: 99%
“…Besides the stabilizing role exerted by PCs on ECs [ 52 , 158 ], there is an active angiogenic effect of PCs in secreting pro-regenerative molecules in response to PDGF-B [ 295 , 296 ]. Of particular note is VEGF, which has been immunolocalized in PCs during human cerebral cortex development [ 174 ] and is released by these cells in in vitro models [ 175 , 296 , 297 ]. In a mathematical, biomimetic 3D angiogenesis model, it has been demonstrated that PCs intervene in the VEGF/TNF-α (tumor necrosis factor-α) proangiogenic/antiangiogenic interplay, promoting a proangiogenic effect of TNF-α, thus allowing complete VEGF-induced sprout formation, elongation, and lumenalization, and also ensuring that the efficacy of the reverted TNF-α effect is proportional to the extension of the pericyte coverage.…”
Section: Human Neocortex and The Developing Nvumentioning
confidence: 99%
“…AIS is mainly caused by cerebral vascular occlusion, which leads to focal neurological deficits [13]. At present, the internationally recognized treatment means is to open occluded blood vessels as soon as possible and reduce ischemic injury of brain tissue [28]. The main treatment methods are thrombolysis and arterial thrombectomy after thrombolysis, but the reperfusion injury to brain tissue after recanalization is one of the main reasons for the poor therapeutic effect [1].…”
Section: Introductionmentioning
confidence: 99%